Testing High-energy Emission Models for Blazars with X-Ray Polarimetry - Peirson Abel L.; Liodakis Ioannis; Romani Roger W. (IOP Publishing Ltd, 2022)
Both leptonic and hadronic emission processes may contribute to blazar jet emission; which dominates in blazars' high-energy emission component remains an open question. Some intermediate synchrotron peaked blazars transition from their low- to high-energy emission components in the X-ray band making them excellent laboratories to probe both components simultaneously, and good targets for the newly launched Imaging X-ray Polarimetry Explorer (IXPE). We characterize the spectral energy distributions for three such blazars, CGRaBS J0211+1051, TXS 0506+056, and S5 0716+714, predicting their X-ray polarization behavior by fitting a multizone polarized leptonic jet model. We find that a significant detection of electron synchrotron dominated polarization is possible with a 300 ks observation for S5 0716+714 and CGRaBS J0211+1051 in their flaring states, while even 500 ks observations are unlikely to measure synchrotron self-Compton (SSC) polarization. Importantly, nonleptonic emission processes like proton synchrotron are marginally detectable for our brightest intermediate synchrotron peaked blazar (ISP), S5 0716+714, during a flaring state. Improved IXPE data reduction methods or next-generation telescopes like eXTP are needed to confidently measure SSC polarization.